The Epic Imaginary - Payne, Charlton (De Gruyter, 2012)
This study analyzes how the imagination of the epic genre as legitimately legitimating community also unleashes an ambivalence between telling coherent - and hence legitimating - stories of political community and narrating open-ended stories of contingency that might de-legitimate political power. Manifest in eighteenth-century poetics above all in the disjunction between programmatic definitions of the epic and actual experiments with the genre, this ambivalence can also arise within a single epic over the course of its narrative. The present study thus traces how particular eighteenth-century epics explore an originary incompleteness of political power and its narrative legitimations. The first chapter sketches an overview of how eighteenth-century writers construct an imaginary epic genre that is assigned the task of performing the cultural work of legitimating political communities by narrating their allegedly unifying origins and borders. The subsequent chapters, however, explore how the practice of epic storytelling in works by Klopstock, Goethe, Wieland, and, in an epilogue, Brentano enact the disruptive potential of poetic language and narrative to question the legitimations of imaginary political origins and unities
10.1515/9783110271997
Keywords: Epic literature; German / History and criticism; German literature / 18th century / History and criticism; Politics and literature / Germany / History / 18th century; 18th-Century German Literature; Brentano; Clemens; C. Brentano; C.M. Wieland; Community; Epic; F.G. Klopstock; Goethe; Johann W. von; J.W. Goethe; Klopstock; Friedrich Gottlieb; Poetik; Political Imaginary; Politisches Denken/i.d. Literatur; Wieland; Christoph Martin; LITERARY CRITICISM / European / German